Life satisfaction among older adults with impairment in activities of daily living. (9th September 2021) - Boccaccio, Dominic E; Cenzer, Irena; Covinsky, Kenneth E
Abstract: Background: Many older adults experience decline in function, but maintain high levels of life satisfaction. The factors associated with high life satisfaction among those with functional impairment are not well understood. Objective: Examine the proportion of older adults with functional impairment reporting high life satisfaction and the predictors of high life satisfaction. Design: Cross-sectional cohort study. Setting: Health and Retirement Study. Subjects: A total of 7, 287 community-dwelling participants, 65 years or older, who completed the leave-behind questionnaire in 2014 or 2016. Methods: The main predictor was having difficulty or needing help in performing Activities of Daily Living (ADL). The primary outcome was reporting high life satisfaction, defined using a three-item Diener scale. Significant factors were identified using modified Poisson regression models adjusted for demographic characteristics. Results: Those with no ADL impairment were more likely to report high levels of life satisfaction than those with ADL difficulty or ADL dependence (54.4 vs 38.6 vs 27.6%, P < 0.001). Among those with ADL dependence, we identified several factors associated with high life satisfaction, including: not being lonely (38.2 vs 23.2%, ARR = 1.6 (1.2, 2.2)), satisfied with family life (35.1 vs 12.8%, ARR = 2.7 (1.6, 4.4)), and satisfied with financial situation (40.8 vs 16.6%, ARR = 2.5 (1.8, 3.6)). Similar associations were present among those with ADL difficulty. Conclusions: A substantial proportion of older adults with ADL impairment report high life satisfaction, and it is associated with social and economic well-being. Understanding the factors associated with high life satisfaction can lead to clinical practices and policy guidelines that promote life satisfaction in older adults.